Intake of dairy foods and risk of Parkinson disease. (4th July 2017) - Hughes, Katherine C.; Gao, Xiang; Kim, Iris Y.; Wang, Molin; Weisskopf, Marc G.; Schwarzschild, Michael A.; Ascherio, Alberto
Abstract : Objective: To prospectively examine the association between commonly consumed dairy products and the risk of Parkinson disease (PD) in women and men. Methods: Analyses were based on data from 2 large prospective cohort studies, the Nurses' Health Study (n = 80, 736) and the Health Professionals Follow-up Study (n = 48, 610), with a total of 26 and 24 years of follow-up, respectively. Both US-based studies were conducted via mailed biennial questionnaires. Dietary intake was assessed with food frequency questionnaires administered repeatedly over the follow-up period. Incident cases of PD (n = 1, 036) were identified via questionnaires and subsequently confirmed by reviewing medical records. We also conducted a meta-analysis to combine our study with 3 previously published prospective studies on total milk intake and PD risk and 1 study on total dairy intake and PD risk. Results: While total dairy intake was not significantly associated with PD risk in our cohorts, intake of low-fat dairy foods was associated with PD risk. The pooled, multivariable-adjusted hazard ratio (HR) comparing people who consumed at least 3 servings of low-fat dairy per day to those who consumed none was 1.34 (95% confidence interval [CI] 1.01–1.79, p trend = 0.04). This association appeared to be driven by an increased risk of PD associated with skim and low-fat milk (HR 1.39, 95% CI 1.12–1.73, p trend <0.01). Results were similar in women and men ( p for heterogeneity >0.05). In the meta-analysis, the pooled relative risk comparing extreme categories of total milk intake was 1.56 (95% CI 1.30–1.88), and the association between total dairy and PD became significant (HR 1.27, 95% CI 1.04–1.55). Conclusions: Frequent consumption of dairy products appears to be associated with a modest increased risk of PD in women and men.